Imbalance of Circulating Tfh/Tfr Cells in Patients With Parkinson's Disease - Zhao, Xiuzhen; Jin, Tao; Zheng, Chao; Ma, Di; Zhang, Ying (Frontiers in Neurology, 2020)
Background: Follicular helper T (Tfh) cells and follicular regulatory T (Tfr) cells are essential for B cell differentiation, germinal center formation, and humoral immune responses. Immunity and inflammation have been thought to be involved in Parkinson’s disease (PD). In this study, we aimed to identify whether circulating Tfh and Tfr (cTfh and cTfr) cells contribute to PD. Methods: Thirty-nine PD patients and 26 health controls (HCs) were enrolled. The numbers of cTfh (CD4+CXCR5+PD-1+) cells and cTfr (CD4+CXCR5+CD25hiCD127low) cells were analyzed via flow cytometry. The serum concentrations of interleukin (IL)-4, IL-10, IL-21, and transforming growth factor (TGF)-β were examined by cytometric bead array. Results: The percentage of cTfh cells among CD4+ T cells in PD patients was significantly higher than that in HCs [3.68% (2.64%–5.70%) vs 1.94% (1.32%–2.99%), P<0.001], while the percentage of cTfr cells among CD4+ T cells in PD patients was slight decreased but without significance [1.05% (0.62%–1.54%) vs 1.3% (0.63%–1.90%), P>0.05]. The percentage of CD19+ B cells in peripheral blood mononuclear cells was significantly lower in PD patients than in HCs [5.35% (4.13%–9.38%) vs 8.68% (5.61%–12.93%), P=0.014]. The serum concentrations of IL-4, IL-10, IL-21, and TGF-β in PD patients did not differ significantly from those in HCs (P>0.05). There was a positive trend of the correlation between the number of cTfh and the serum IL-4 concentrations in PD patients (P=0.032, r=0.353). There was a positive trend of the correlation between the number of cTfr and the serum IL-10 concentrations in PD patients (P=0.047, r=0.328). A positive trend of the correlation were found for the serum concentration of IL-21 with H-Y stage (r=0.356, P=0.026) and UPDRS-III score (r=0.347, P=0.030). Conclusions: These results indicate that an imbalance of cTfh and cTfr cells may be involved in the chronic progression of PD, and IL-21 may be a biomarker for monitoring the severity of this disease.